2022
DOI: 10.14314/polimery.2022.5.4
|View full text |Cite
|
Sign up to set email alerts
|

A new polysaccharide-based ion-exchange resin for industrial wastewater treatment

Abstract: A new ion-exchange resin was obtained by incorporating a tripropylamine group into a tamarind polysaccharide resin (TTA). The TTA resin was characterized by FTIR, elemental analysis, and other physicochemical properties. The influence of pH, treatment time and resin concentration on the adsorption of metal ions from industrial wastewater was investigated. It was found that the obtained TTA resin effectively removes heavy metal ions in the following order: Fe2+> Cu2+> Zn2+> Cd2+> Pb2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…By maintaining a constant stirring speed (150 rpm), pH (7), and temperature (27 • C), it was observed that an increase in the contract time from 30 min to 240 min increased the rate of adsorption of the metal ions to the H-TTAPA resin. The presence of large functional groups in the H-TTAPA resin significantly increases the binding capacity, thus helping to accelerate the process [56].…”
Section: Effect Of Contact Time On the Removal Of Metal Ionsmentioning
confidence: 99%
“…By maintaining a constant stirring speed (150 rpm), pH (7), and temperature (27 • C), it was observed that an increase in the contract time from 30 min to 240 min increased the rate of adsorption of the metal ions to the H-TTAPA resin. The presence of large functional groups in the H-TTAPA resin significantly increases the binding capacity, thus helping to accelerate the process [56].…”
Section: Effect Of Contact Time On the Removal Of Metal Ionsmentioning
confidence: 99%
“…DMF was used to swell the resin. To make a homogenous layer, the swelling resin was allowed to settle 40 . The height of the column was about 4-5 cm, and the resin utilised was roughly 5.0 gram.…”
Section: Binary Seperation Of Cu(ii) and Cr(iii) Mixtures Using Taba ...mentioning
confidence: 99%